2010
DOI: 10.1007/s12289-010-0753-9
|View full text |Cite
|
Sign up to set email alerts
|

Hole expansion of advanced high strenth steel sheet sample

Abstract: In this work, the stretch-flangeability of an AHSS steel sheet sample, TWIP1000, was investigated through the hole expansion tests. Uniaxial tension and disk compression tests were also performed to characterize the basic mechanical behaviour of the material. Then finite element simulations of the hole expansion test were carried out using ABAQUS, respectively combined with three yield criteria, Von Mises, Hill 1948 and Yld2000-2d. Finally, the simulation results were compared with experimental to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Several testing procedures have been designed to study sheet metal forming. Among them, Nakazima [14] and Marciniak tests are probably the most popular and are defined by international standards such as ASTM E2218-02 and ISO 12004-2:2008 [25][26][27]. Following these tests, specimens with different geometries are placed in a stamping press or a testing device equipped respectively with hemispherical or cylindrical punches [28][29][30].…”
Section: Experimental Procedures For Determination Of Fld Using Multi-axial Tensile Testsmentioning
confidence: 99%
“…Several testing procedures have been designed to study sheet metal forming. Among them, Nakazima [14] and Marciniak tests are probably the most popular and are defined by international standards such as ASTM E2218-02 and ISO 12004-2:2008 [25][26][27]. Following these tests, specimens with different geometries are placed in a stamping press or a testing device equipped respectively with hemispherical or cylindrical punches [28][29][30].…”
Section: Experimental Procedures For Determination Of Fld Using Multi-axial Tensile Testsmentioning
confidence: 99%
“…Considering that the microstructure of the steels is intrinsically crystal-like, the crystallographic features should exert a non-ignorable action on the HER. Although present studies [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ] have concluded that the crystallographic characteristics (primarily for anisotropy or textures) will alter the stretch-flange-formability, the intrinsic aspect of variant pairing characteristics was omitted in these researches as a result of the absence of deep analytical methods. However, it is possible [ 24 , 25 , 26 , 27 ] now.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], the influential aspects of HER include the deformation details, the punch geometries, the tensile properties, and the microstructure of the steel sheet [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, most steel researchers focus on the material itself, and a considerable number of experimental and simulation works [ 4 , 9 , 11 ] have been done on the effect of the microstructure to the HER, respectively, for the aspects of the phases constituting the microstructure [ 5 , 10 , 12 , 14 ] the anisotropy [ 15 , ...…”
Section: Introductionmentioning
confidence: 99%
“…To predict the edge cracks of AHSS sheets during the stamping and flanging process, hole punching and expansion tests (which are common methods to evaluate edge stretchability) are utilized in industries for estimating the quantitative amounts of edge fracture resistance [8,9]. The hole expanding process, which is defined in the ISO 16630-2009 standard, consists of punching a hole on a test specimen and using a conical punch with 60 degrees at the top which moves upward to extend through the thickness of the AHSS sheets [10].…”
Section: Introductionmentioning
confidence: 99%